2021
DOI: 10.1073/pnas.2015873118
|View full text |Cite
|
Sign up to set email alerts
|

Time-restricted feeding protects the blood pressure circadian rhythm in diabetic mice

Abstract: The quantity and quality of food intake have been considered crucial for peoples' wellness. Only recently has it become appreciated that the timing of food intake is also critical. Nondipping blood pressure (BP) is prevalent in diabetic patients and is associated with increased cardiovascular events. However, the causes and mechanisms of nondipping BP in diabetes are not fully understood. Here, we report that food intake and BP were arrhythmic in diabetic db/db mice fed a normal chow diet ad libitum. Imposing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 60 publications
8
44
0
Order By: Relevance
“…Previous studies demonstrated that SNS activity is suppressed during fasting and enhanced after feeding ( 11 15 ). Consistent with these studies, we recently reported that the non-dipping BP is associated with diminished rhythms of food intake and SNS activity in diabetic db/db mice ( 16 ). Importantly, we demonstrated that aligning food availability with the standard light-dark cycle by dark-phase TRF, which limits food availability only to the active dark phase, restores BP and SNS activity rhythms in db/db mice ( 16 ).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Previous studies demonstrated that SNS activity is suppressed during fasting and enhanced after feeding ( 11 15 ). Consistent with these studies, we recently reported that the non-dipping BP is associated with diminished rhythms of food intake and SNS activity in diabetic db/db mice ( 16 ). Importantly, we demonstrated that aligning food availability with the standard light-dark cycle by dark-phase TRF, which limits food availability only to the active dark phase, restores BP and SNS activity rhythms in db/db mice ( 16 ).…”
Section: Introductionsupporting
confidence: 77%
“…Consistent with these studies, we recently reported that the non-dipping BP is associated with diminished rhythms of food intake and SNS activity in diabetic db/db mice ( 16 ). Importantly, we demonstrated that aligning food availability with the standard light-dark cycle by dark-phase TRF, which limits food availability only to the active dark phase, restores BP and SNS activity rhythms in db/db mice ( 16 ). However, whether SNS activity rhythm serves as the mechanistic linkage between light-phase TRF and BP circadian rhythm alteration has not been investigated.…”
Section: Introductionsupporting
confidence: 77%
“…It should be noted that a recent study in mice showed that the blood pressure rhythm could be inverted by restriction of food intake to the inactive period, and this effect occurred in the absence of changes in the diurnal pattern of urinary sodium excretion ( 104 ). In a pathophysiological setting, it was recently shown that restricting food intake to the active period restored the normal blood pressure rhythm in non-dipping, diabetic mice ( 105 ). In a clinical study, 642 Chinese adults with primary hypertension underwent 24-hour ambulatory blood pressure monitoring, and 24-hour urine sodium excretion was measured along with morning urine sodium concentration ( 106 ).…”
Section: Circadian Disruption In Diseases Of the Human Kidneymentioning
confidence: 99%
“…Although not directly compared, the hyperacetylation exhibited in the HF diet islet may be partially driven by disruption in the circadian feed-fast cycle which occur with HF feeding ( 159 ). The leptin receptor deficiency model of T2DM (Lepr db/db ), which also exhibits impaired circadian food intake rhythms ( 160 ), similarly exhibits increased H3K27ac and histone H3 lysine 4 monomethylation (H3K4me1; activating chromatin mark which co-occurs with H3K27ac) signal in regions associated with feeding but not in regions associated with fasting. Importantly, regions hyperacetylated are associated with LSD1 binding where it acts as a brake on transcription by demethylating H3K4, likely contributing to β-cell rest ( 161 ).…”
Section: Islet Response To Time-dependent Regulation Of Food Intakementioning
confidence: 99%